Time division multiple access for vehicular communications - Omar, Hassan Aboubakr (SpringerBriefs in Computer Science, 2014)
This brief focuses on medium access control (MAC) in vehicular ad hoc networks (VANETs), and presents VeMAC, a novel MAC scheme based on distributed time division multiple access (TDMA) for VANETs. The performance of VeMAC is evaluated via mathematical analysis and computer simulations in comparison with other existing MAC protocols, including the IEEE 802.11p standard. This brief aims at proposing TDMA as a suitable MAC scheme for VANETs, which can support the quality-of-service requirements of high priority VANET applications.